Structural and magnetic properties of LaCrO3 half-doped with Al. Issue 13 (October 2016) - Silva, Romualdo S.; Barrozo, Petrucio; Moreno, N.O.; Aguiar, J. Albino
Abstract: Structural and magnetic properties of LaCrO3 half-doped with Al are reported in this work. Pure and half-doped samples were prepared by combustion synthesis using urea as fuel. The crystal structure was investigated by X-ray diffraction and Rietveld analysis. A structural phase transition caused by a decrease of the chemical pressure was observed. The scanning electron microscopy (SEM) images show the formation of porous samples with particles of irregular morphologies. A quantitative Energy-dispersive X-ray spectroscopy (EDS) analysis on the surface indicates the inclusion of the Al on the structure. However, a small deficiency of La and Al was observed. Magnetization measurements as a function of temperature reveal an antiferromagnetic order in both samples. A large decrease of TN (Néel temperature) and a reduction of the frustration factor is observed in the sample doped with Al. The magnetic isothermal at 5 K shows a typical antiferromagnetic behavior with a slightly spin canting for the doped sample.